Experience of “Purple code” to Manage COVID-19 Pregnant Women - Laura Marcela Cano Murillo; Lenny Piña Guerrero; Betsy Corina Sosa García; Miriam Deyanira Rodríguez Piña; Verónica Gil Venadero; Hugo Mendieta Zerón; Carlos Arturo Paniagua Coahuila (HEALTH SCIENCES AND DISEASE, 2022)
ABSTRACT Objective. The world is facing a SARS-CoV-2 coronavirus pandemic. One of the greatest challenges of the current pandemic is its high speed of transmission, such that its global spread has caused more deaths than its predecessors along with the collapse of health services. Patients and Methods. This retrospective, cross-sectional study performed on the second half of 2020 was designed to describe the experience in managing COVID-19 pregnant women through a logistic called “Purple code”. Results. During the study period, 70 women (mean age 24.33 years old) were subjected to be managed under the “purple code”. Gestational age <35 WG prevailed in the study. The analysis showed that the most frequent procedures performed in the toco-surgery service were cesarean section (91%), followed by natural childbirth (7%), instrumented uterine curettage (1%), and tracheostomy (1%). Among the health staff involved in the direct treatment of the patients there were no fatal cases or hospitalizations. Discussion. The protocol established in the HMPMPS is in accordance with the recommendations of international guidelines for maternal and perinatal care, preventing at the same time the risk of infection in the health staff. Conclusions. A positive impact has been achieved in the case management of patients with COVID-19 where strict and rigorous measures were established, classified as “purple code”. RÉSUMÉ Objectif. Le monde est confronté à la pandémie de coronavirus SARS-CoV-2. L'un des plus grands défis de la pandémie actuelle est sa vitesse de transmission élevée, de sorte que sa propagation mondiale a causé plus de décès que ses prédécesseurs ainsi que l'effondrement des services de santé. Patients et Méthodes. Cette étude rétrospective et transversale réalisée sur le second semestre 2020 a été conçue pour décrire l'expérience de prise en charge des femmes enceintes COVID-19 à travers une logistique appelée "Code Violet". Résultats. Au cours de la période d'étude, 70 femmes (âge moyen 24,33 ans) ont été soumises à une prise en charge sous le « Code Violet ». L'âge gestationnel <35 SA a prédominé dans l'étude. L'analyse a montré que les actes les plus fréquemment pratiqués dans le service de toco-chirurgie étaient la césarienne (91%), suivie de l'accouchement naturel (7%), du curetage utérin instrumenté (1%) et de la trachéotomie (1%). Parmi le personnel de santé impliqué dans le traitement direct des patients, il n'y a eu aucun cas mortel ou d’hospitalisation. Discussion. Le protocole établi dans le HMPMPS est conforme aux recommandations des lignes directrices internationales pour les soins maternels et périnataux, prévenant en même temps le risque d'infection chez le personnel de santé. Conclusion. Un impact positif a été obtenu dans la prise en charge des patients atteints de COVID-19 où des mesures strictes et rigoureuses qualifiées de « Code Violet » ont été établies.